Premature Ejaculation: Proposed Diagnostic Criteria, A Letter to Editor - A V, RAVEENDRAN (Archives of Men's Health, 2022)
Premature Ejaculation (PE) is a common male sexual dysfunction. But its diagnosis is still a challenge for clinicians (1). People are either reluctant to approach doctors with their sexual problems or those who approach health care providers are reluctant to ask for proper history (2). Although being the most common sexual dysfunction, there is no clear-cut case definition or criteria for the clinical diagnosis which can be used in day-to-day practice.